2004
DOI: 10.2174/0929867043363721
|View full text |Cite
|
Sign up to set email alerts
|

Furocoumarins in Medicinal Chemistry. Synthesis, Natural Occurrence and Biological Activity

Abstract: The scope of this review encompasses the importance of furocoumarins and the most important developments in this field that have been made in recent years, with particular emphasis placed on the aspects related to medicinal chemistry. A concise and exhaustive overview is given regarding the methods used for the synthesis of these compounds, new furocoumarins isolated from natural sources, and the most significant biological properties associated with these molecules. The section describing the synthetic method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(86 citation statements)
references
References 111 publications
0
85
0
1
Order By: Relevance
“…27 Furocoumarins are a class of natural and synthetic compounds used as photoreactive, antiviral, antiinflammatory agents as well as kinase inhibitors. 28 Furo [4,3-c]coumarins are generally prepared by condensation of aryl substituted 4-hydroxycoumarins as dinucleophiles and vicinal dielectrophiles. 26,29 In a quest for new anti-inflammatory / antiallergic therapeutics we screened our compound collection in mast cell degranulation assays and leukotriene B 4 assay.…”
Section: This Results Implied An Anti-allergic Action Of Cnidicin In Vmentioning
confidence: 99%
“…27 Furocoumarins are a class of natural and synthetic compounds used as photoreactive, antiviral, antiinflammatory agents as well as kinase inhibitors. 28 Furo [4,3-c]coumarins are generally prepared by condensation of aryl substituted 4-hydroxycoumarins as dinucleophiles and vicinal dielectrophiles. 26,29 In a quest for new anti-inflammatory / antiallergic therapeutics we screened our compound collection in mast cell degranulation assays and leukotriene B 4 assay.…”
Section: This Results Implied An Anti-allergic Action Of Cnidicin In Vmentioning
confidence: 99%
“…Bunun yanında, sentetik olarak da üretilen furokumarinler bulunmaktadır. 36,37 Furokumarinler, lineer (Psöralen türevleri) ve angular furokumarinler (Anjelisin türevleri) olarak iki grup altında incelenmektedirler. 38 Furokumarinler, psöriyazis ve vitiligo gibi farklı cilt rahatsızlıklarına karşı fotokimyasal tedavilerde, geniş şekilde kullanılmaktadır.…”
Section: Senteti̇k üRünlerunclassified
“…namely kynurenic acid (1), alaschanioside C (2), umbelliferone (3), bergaptol-O-␤-d-glucopyranoside (4), nodakenin (5), oxypeucedanin (6), bergapten (7), diosmetin (8), oxypeucedanin hydrate (9), O-prenyl-umbelliferone (10), phellopterin (11) and isoimperatorin (12) were isolated in our laboratory from the seeds of N. incisum and N. franchetii and their structures ( Fig. 1) were elucidated by comparison of UV, MS, 1 H NMR and 13 C NMR spectral data with the literature values [4,5,[23][24][25][26][27][28][29].…”
Section: Chemicals and Materialsmentioning
confidence: 99%
“…The chemical constituents from the rhizomes and roots of the two plants were coumarins, phenoloids and essential oils [3][4][5][6][7][8][9]. Pharmacological studies have shown that coumarins such as isoimperatorin, notopterol and bergapten possess anti-inflammatory, analgesic and anti-cancer activities [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%